Toward Integration of mHealth in Primary Care in the Netherlands: A Qualitative Analysis of Stakeholder Perspectives - Bally, Esmee L. S.; Cesuroglu, Tomris (Frontiers in Public Health, 2020)
Background: There is a growing need to structurally change the way chronic illness care is organised as health systems struggle to meet the demand for chronic care. mHealth technologies can alter traditional approaches to healthcare provision by stimulating self-management of chronically ill patients. The aim of this study was to understand the complex environment related to the introduction of mHealth into primary care for chronic disease management while considering health system functioning and stakeholder views. Methods: A transdisciplinary approach was used informed by the Interactive Learning and Action (ILA) methodology. Exploratory interviews (n=5) were held with representatives of stakeholder groups to identify and position key stakeholders. Subsequently, professionals and chronically ill patients were consulted separately to elaborate on the barriers and facilitators in integration, using semi-structured interviews (n=17) and a focus group (n=6). Follow-up interviews (n=5) were conducted to discuss initial findings of the stakeholder analysis. Results: Most stakeholders, in particular primary care practitioners and patients, seem to have a supporting or mixed attitude towards integration of mHealth. On the other hand, several powerful stakeholders, including primary care information system developers and medical specialists are likely to show resistance or a lack of initiative towards mHealth integration. Main barriers to mHealth integration were: a lack of interoperability with existing information systems; difficulties in financing mHealth implementation; and limited readiness in general practices to change. Potential enablers of integration included co-design of mHealth solutions and incentives for pioneers. Conclusion: Stakeholders acknowledge the benefits of integrating mHealth in primary care. However, important barriers perceived by end-users prevent them to fully adopt and use mHealth. This study shows that the complexity of introducing mHealth into primary care calls for strategies encouraging collaboration between multiple stakeholders to enhance successful implementation.